YAP/TAZ regulates TGF-β/Smad3 signaling by induction of Smad7 via AP-1 in human skin dermal fibroblasts - Zhaoping Qin; Wei Xia; Gary J. Fisher; John J. Voorhees; Taihao Quan (Cell Communication and Signaling, 2018)
Abstract Background Transcription factors YAP and TAZ function as the primary mediators of the Hippo pathway. Yet, crosstalk of YAP and TAZ with other signaling pathways remains relatively unexplored. We have explored the impact of YAP and TAZ levels on the TGF-β/Smad signaling pathway in human skin dermal fibroblasts. Methods YAP and TAZ levels in dermal fibroblasts were reduced in dermal fibroblasts by siRNA-mediated knockdown. The effects of YAP and TAZ reduction on TGF-β/Smad signaling were examined by quantitative real-time PCR, Western analysis, and immunostaining. Luciferase reporter assays and electrophoretic mobility shift assays were conducted to investigate the transcription factor DNA-binding and transcriptional activities. Results Knockdown of both YAP and TAZ (YAP/TAZ), but not either separately, impaired TGF-β1-induced Smad3 phosphorylation and Smad3 transcriptional activity, thereby inhibiting the expression of TGF-β target genes. This reduction by reduced levels of YAP/TAZ results from induction of inhibitory Smad7, which inhibits Smad3 phosphorylation and activity by TGF-β1. Conversely, prevention of Smad7 induction restores Smad3 phosphorylation and Smad3 transcriptional activity in fibroblasts that have reduced YAP/TAZ. In agreement with these findings, inhibition of YAP/TAZ transcriptional activity, similar to the reduction of YAP/TAZ levels, also significantly induced Smad7 and impaired TGF-β/Smad signaling. Further investigations revealed that reduced levels of YAP/TAZ led to induction of activator protein-1 (AP-1) activity, Activated AP-1 bound to DNA sequences in the Smad7 gene promoter, and deletion of these AP-1 binding sequences substantially reduced Smad7 promoter reporter activity. Conclusion YAP/TAZ functions in concert with transcription factor AP-1 and Smad7 to regulate TGF-β signaling, in human dermal fibroblasts. Reduction of YAP/TAZ levels leads to activation of AP-1 activity, which induces Smad7. Smad7 suppresses the TGF-β pathway.